Damage assessment of reinforced concrete beams including the load environment - Zhu, X.; Law, S.; Hao, Hong (Techno Press, 2009)
Quantitative condition assessment of structures has been traditionally using proof load test leading to an indication of the load-carrying capacity. Alternative approaches using ultrasonic, dynamics etc. are based on the unloaded state of the structure and anomalies may not be fully mobilized in the load resisting path and thus their effects are not fully included in the measured responses. This paper studies the effect of the load carried by a reinforced concrete beam on the assessment result of the crack damage. This assessment can only be performed with an approach based on static measurement. The crack damage is modelled as a crack zone over an area of high tensile stress of the member, and it is represented by a damage function for the simulation study. An existing nonlinear optimization algorithm is adopted. The identified damage extent from a selected high level load and a low load level are compared, and it is concluded that accurate assessment can only be obtained at a load level close to the one that creates the damage.